Eulogische Sinngestalt und Feiergestalt unfehlbarer Aussagen - Lies, Lothar (Zeitschrift für katholische Theologie, 2001)
We are looking for a theological "paradigma" – including the four "Notae ecclesiae" and demonstrating against Rationalism, Papalism, Fundamentalism and Legalism the deeper sense of infallible theaching in/of the catholic church. We recognize this paradigma in the biblical and patristical understanding of "Berakah" (benediction) with the four structural elements of Anamnesis, Epiklesis, Koinonia and Prosphora.